Electromagnetic waves - Staelin, David H. (Prentice Hall, 1994)
This introduction to electromagnetic waves emphasizes concepts, examples, and problem-solving techniques having wide applicability, and relies only on basic physics and mathematics - rather than electrostatics, magnetostatics, and quasitatics. The focus is on generic problem-solving techniques - both mathematical and physically-intuitive, and the presentation of basic electromagnetic theorems - Poynting, energy, uniqueness, and reciprocity - explained from a physical perspective. Progresses from simple wave propagation in unbounded free space to antenna and resonator design. Presents the fundamental concepts of plane waves, phasors, polarization, energy, power, and force early - and repeatedly applies them throughout the text to problems with progressively more complex boundary conditions. For students and practicing engineers interested in electromagnetic wave phenomena.